PENGARUH LINGKUNGAN DAN STRES KERJA TERHADAP KINERJA KARYAWAN INDUSTRI TURUNAN PARIWISATA (Studi pada RM Sederhana dan Nasi Kapau) - Asman Abnur; Agung Edy Wibowo; Muhamad Nur Afriandi Nasution; Hendra Syaiful (JURSIMA (Jurnal Sistem Informasi dan Manajemen), 2023)
This study intends to find out and analyze the performance of employees in tourism derivative industry into a micro-study in terms of environmental aspects and work stress at the Sederhana and Nasi Kapau restaurants in Batam City. The modern world has placed tourism as a new industry which able in organizing and producing a country's economic growth faster, because it is capable of providing employment, increasing income, increasing living standards and providing stimuli for the productive sectors around it. As part of the derivatives of tourism industry, both of these restaurants provide an interesting phenomenon because they are always full of consumer, either weekdays and especially at holidays. The research variables consist of work environment and work stress as independent variables and performance as the dependent variable. The number of samples was 117 respondents and data analysis using multiple regression. The results showed that work environment has a significant influence on employee performance. Work stress has a significant effect on employee performance. The work environment has a dominant influence on employee performance compared to the effect of work stress on employee performance